2007
DOI: 10.2174/1874325000701010013
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of Periacetabular Osteotomy Using a Two-Incision Approach

Abstract: Abstract:In residual hip dysplasia periacetabular osteotomy (PAO) can improve insufficient coverage of the femoral head. It requires a broad dissection of the pelvic bones and detachment of muscle insertions, however. We have developed a modification of the Bernese periacetabular osteotomy with reduced soft tissue exposure. It uses two small skin incisions and offers therefore the perspective of nicer scars but also increases the risk of technical complications due to impaired vision. To be able to draft these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 23 publications
1
37
0
5
Order By: Relevance
“…This was similar the finding of Bernstein et al [2] and Troelsen et al [23] who both reported similar acetabular correction normalization between groups with standard versus minimally invasive approaches.…”
Section: Limitationssupporting
confidence: 90%
See 3 more Smart Citations
“…This was similar the finding of Bernstein et al [2] and Troelsen et al [23] who both reported similar acetabular correction normalization between groups with standard versus minimally invasive approaches.…”
Section: Limitationssupporting
confidence: 90%
“…Recent studies have described alternative approaches to the Bernese PAO in the hopes of decreasing complications, surgical time, surgical trauma, estimated blood loss, and length of stay (LOS) while maintaining the ability to reorient the acetabulum [2,14,19,23]. Based on these reports, we began modifying the standard Bernese PAO with a rectus femoris-sparing surgical approach without arthrotomy for PAO in 2012.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Although minimally invasive surgery is commonly used in THAs [8, 19, 22], there are only a few reports regarding minimally invasive surgery for acetabular reorientation osteotomy [2, 20, 28, 29]. There are several reports regarding acetabular redirectional osteotomies for hip dysplasia, such as the triple osteotomy [24], dial osteotomy [14], double osteotomy [25], spherical osteotomy [33], rotational osteotomy [18, 26, 27], and periacetabular osteotomy [7], which are recognized standard surgical procedures for early stages of degenerative osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%